2021
DOI: 10.1002/smj.3293
|View full text |Cite
|
Sign up to set email alerts
|

CEO early‐life disaster experience and corporate social performance

Abstract: Research Summary Despite an extensive upper echelons literature on how CEOs' prior experiences influence firm behavior, we know little about the influence of traumatic experiences early in CEOs' lives. Drawing on post‐traumatic growth theory, we describe how traumatic experiences early in CEOs' lives influence corporate social performance. Our theory points to the asymmetric impact of CEO early‐life trauma on responsible and irresponsible corporate social performance and to two boundary conditions: CEO age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 113 publications
(182 reference statements)
6
80
0
Order By: Relevance
“…Although the sent-down experience has its specific historical context, and may not replicate elsewhere, this particular experience is possibly generalizable to any hardship experienced by adolescents that are out of their control. Thus, our study may help understand the role that such adversities, experienced by senior executives, play in firm internationalization, which adds to the research on CEO early-life in echoing the call from O’Sullivan and Zolotoy (2021) .…”
Section: Conclusion and Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although the sent-down experience has its specific historical context, and may not replicate elsewhere, this particular experience is possibly generalizable to any hardship experienced by adolescents that are out of their control. Thus, our study may help understand the role that such adversities, experienced by senior executives, play in firm internationalization, which adds to the research on CEO early-life in echoing the call from O’Sullivan and Zolotoy (2021) .…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…Studies in developmental psychology demonstrate that imprints from early-life experiences can be formative and enduring and manifest in various subsequent decisions ( Caspi et al, 2005 ). Prior studies in management literature have investigated the role of CEO early-life poverty ( Xu and Li, 2016 ), early-life disaster experience ( O’Sullivan and Zolotoy, 2021 ) on firm strategies such as CSR and innovation, yet little is known about the impact of CEO early-life adversity instigated by social disorder. Using the send-down movement in china as the context of individual adversity, we analyze how CEO early-life adversity experience might affect their tolerance of uncertainty and change self-efficacy and then influence firm internationalization performance, enriching the stream of research on how senior executives’ early-life experiences influence firm strategies and outcomes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that childhood experiences contribute to the development of an individual’s character and will continue to influence moral judgment and value orientation. Early life experiences of poverty have a stronger impact on a CEO and are more likely to develop a sense of social responsibility and morality, such as greater compassion ( Malmendier et al, 2011 ) and an increased sense of responsibility ( O’Sullivan et al, 2021 ; Xu and Ma, 2021 ). According to Feng and Johansson (2018) , CEOs who experienced the Great Chinese Famine in their youth were less likely to commit fraud and showed higher levels of ethics ( Feng and Johansson, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Early life experiences of poverty can influence executives’ cognitive structure, decision-making preferences, value orientations, and so on ( Holman and Silver, 1998 ; Pandya, 2020 ; O’Sullivan et al, 2021 ). This influence is “imprinted” as cognitive habits and behavioral characteristics, persistent in the subconscious of executives and reflected in their decisions ( Marquis and Tilcsik, 2013 ).…”
Section: Introductionmentioning
confidence: 99%